Optimasi Proses pirolisis dari Kulit Kayu Akasia Crassicarpa Menjadi Bio-Char menggunakan Metode Respon Surface Methodologi Central Composite Design - Darmiyati, Siti; Bahri, Syaiful; Sunarno, Sunarno (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2025)
The problem of fossil energy crisis and the increasing carbon emissions have encouraged the search for environmentally friendly alternative energy sources, one of which is through the utilization of biomass into solid fuels such as bio-char. This study aims to optimize the pyrolysis process conditions to produce high-quality bio-char from Acacia crassicarpa bark, a lignocellulosic waste from the forestry industry. The pyrolysis process was carried out in a batch reactor with variations in temperature (400–500°C), residence time (30–60 minutes), and NiMo/NZA catalyst concentration (2–6%) as independent variables. Optimization was carried out using the Response Surface Methodology approach with a Central Composite Design experimental design to obtain the optimum conditions. The results showed that the optimum conditions were obtained at a pyrolysis temperature of 400°C, residence time of 30 minutes, and catalyst concentration of 2%, resulting in a bio-char yield of 33.8% with a desirability value of 0.876. Meanwhile, the highest calorific value of 28 MJ/kg was achieved at the same temperature with a residence time of 90 minutes. This value exceeds the minimum standard for solid fuels according to the International Biochar Initiative and the European Biochar Certificate, which are generally in the range of >20–25 MJ/kg. Thus, the resulting bio-char not only has potential as an alternative energy source but also meets quality standards as an efficient and sustainable solid fuel.